From Forced Migrants to Necessity Entrepreneurs: The Case of Refugees from Syria in Lebanon - Doraï, Kamel (CCSD, 2022)
International audience Protracted refugees such as Palestinians or more recently Syrians are particularly impacted by the different crises affecting Lebanon. Most of them have a limited access both to assistance and protection, and are confined to low-paying competitive sectors. The main objective of this article is to analyze the response of refugee populations to their economic precariousness in urban areas, taking into account the multiplicity of statuses and the diversity of situations (refugees, illegal workers, etc.). If the crisis affects all foreign workers in a precarious situation, access to certain resources (international, local assistance, etc.) combined with their precarious legal status largely condition their ability to resist. This presentation will focus on the strategies developed by the refugees to adapt to the constraints. I will analyze the development of “necessity entrepreneurship” as a strategy to generate income. Necessity entrepreneurship can be defined as following: when someone is forced by lack of job opportunities to develop his own business for economic survival.